Polusi Dan Saham : Investigasi Dampak Emisi Gas Rumah Kaca Terhadap Return Saham - Putri Dwi Yanti; Zayyan Ahmad Nuryaddin; Isnalita Isnalita (Owner : Riset dan Jurnal Akuntansi, 2025)
This study examines the impact of greenhouse gas (GHG) emission levels on stock returns of companies listed on the Indonesia Stock Exchange during the period 2018-2022. Using the Ordinary Least Squares (OLS) method and data from the Osiris and Bloomberg databases, this study analyzes a sample of 146 companies. The results show that GHG emissions have a significant negative impact on stock returns. These findings underscore that investors consider GHG emissions as an indicator of environmental risk in their investment decisions. The study also highlights the importance of transparency in emission reporting to attract sustainable investments. Limitations of this study include the scope of data limited to public companies in Indonesia. Therefore, further research with a larger sample and more comprehensive emission data is needed.